PRODUCT QUALITY IMPROVEMENT USING SIX SIGMA APPROACH IN YARN MAKING PROCESS IN PT. SUTRA COTTON TEXTILE INDUSTRIES SURABAYA - Matias Kurnia Widyanto (UNIPA PRESS, 2020)
The successful implementation of the six sigma quality improvement program is demonstrated through the improvement of the capability process in producing products leading to zero defect. Therefore, the concept of calculating process capability is very important to understand in the implementation of the Six Sigma program. This research raises the problem of the low level of capability process in producing yarns at PT. Sutra Cotton Textile Industries, Surabaya. By wisely applying six sigma techniques can help reduce things that can affect overall costs. If a company has successfully implemented the concepts in six sigma, then it can be ascertained that the company is truly a reliable company in the world class. Another advantage gained from the implementation of the Six Sigma program is the achievement of targets, namely the increased capability process, of course, in terms of cost. From secondary data in May 2019, in the measure phase it is known that the DPMO value of 16,266 which can be interpreted that of one million production carried out there was a defect of 16,266 with a sigma value of 3.64. From these results it can be said that the production process in Winding has not been able to produce products that fit the desired specifications and is still lagging behind other subprocesses. method. The main priority in carrying out corrective actions based on FMEA is to clean and check the machine at the end of each production cycle. From the results of improvements, the sigma value and DPMO value obtained in September 2019 is 10,977 DPMO which means that of one million production carried out there is a defect of 10,977 with a sigma value of 3.80.